Retrieving the relative contribution of aerosol types from single particle analysis and radiation measurements and calculations: A comparison of two independent approaches - Achad, Mariana (2013)
The main purpose of this work is to determine the relative contribution of different types of aerosols at an urban site by using two independent approaches: individual particle analysis, and radiative transfer calculations and irradiance measurements. To accomplish that purpose, we used our UV-B irradiance (280–315 nm) data set, the AERONET (AErosol RObotic NETwork) database, the SEM (Scanning Electron Microscopy, LEO 1450VP) analyses of the collected particles and the Santa Barbara DISORT Atmospheric Radiative Transfer (SBDART) model. On one hand, the collected particles were analyzed by SEM-EDX (Energy Dispersive X-Ray, Genesis 2000) in order to determine their chemical composition. Then, by using a developed algorithm they were classified as rural or urban, resulting in a (24±3)% of rural and (76±8)% of urban. On the other hand, aerosols were incorporated into the SBDART model through two of its default profiles (urban or rural) and by using the Aerosol Optical Depth (AOD) provided by AERONET. The aerosol effect on experimental surface UV-B irradiance was reproduced by a linear combination of the irradiances calculated by using these profiles. From this analysis we found that, in average, a mix of aerosols of (30±3)% rural and (70±7)% urban explains the observed reduction in the experimental irradiance. Considering the agreement between the results obtained by using these two independent methodologies, the use of the irradiance as a surrogate variable to retrieve aerosol types is discussed. The methodology presented here is applicable to any site provided irradiance measurements and AOD are available.